Key to health - Gandhi, M.K. (Ahmedabad Navajivan, 2023)
In this book, Mahatma Gandhi shares his timeless ideas on maintaning good health without having to resort to doctors or medicines. As he elaborates, this is possible by utilising nature's elements such as fresh air, pure water, natural foods and following common-sense principles in the matters of diet, exercise and sleep. Originally written in Gujarati and translated in to English by Sushila Nagar, his personal physician, Gandhi wrote this book when he was incarcerated in the Aga Khan Palace, Poona, during 1942-44. Seven decades have passed since this book was written, but it continues to be relevant and applicable even today.
Keywords: Health ideologies- M.K. Gandhi